Critical thinking in integrated language learning on elementary schools - Muzaki, Ferril Irham (SCIENCE PRESS, 2024)
Elementary school years present a high window for language accession. This period offers a unique occasion to integrate critical thinking chops alongside language literacy. This approach fosters a deeper understanding of language, empowering scholars to become active actors in their literacy trip. By encouraging analysis, evaluation, conclusion, and problem- working within a language learning environment, preceptors equip scholars with the tools to navigate complications and develop a stronger foundation in language structures. Critical thinking in language literacy fosters not only bettered communication chops but also cultivates transmittable chops applicable across academic disciplines. Likewise, it naturally motivates scholars, encouraging tone- directed literacy and a lifelong love of language disquisition. This abstract highlight the significance of integrating critical thinking into abecedarian language literacy, emphasizing its impact on communication chops, transmittable capacities, and the development of lifelong learners. Keywords: Critical thinking, language acquisition, elementary education, second language learning (SLL), transferable skills, lifelong learning